2018
DOI: 10.18632/oncotarget.25650
|View full text |Cite
|
Sign up to set email alerts
|

Survivin as a potential therapeutic target of acetylsalicylic acid in pituitary adenomas

Abstract: Acetylsalicylic acid (ASA) is known as a cancer preventing agent, but there is no data available regarding the effect of ASA on pituitary cells.We investigated 66 nonfunctioning (NFPA) and growth hormone (GH)-producing adenomas and 15 normal pituitary samples. Functional assays (cell viability, proliferation, flow cytometry cell cycle analysis, caspase-3 activation and DNA degradation) were applied to explore the effect of ASA, YM155 (survivin inhibitor), survivin-targeting siRNA and TNF-related apoptosis-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…potential of drugs for treatment of pituitary adenomas [22]. In the current study we aimed to investigate the expression of different subunits of acetylcholine receptors.…”
Section: Plos Onementioning
confidence: 99%
“…potential of drugs for treatment of pituitary adenomas [22]. In the current study we aimed to investigate the expression of different subunits of acetylcholine receptors.…”
Section: Plos Onementioning
confidence: 99%
“…Peptides presented in human body fluids, cells, and tissues, and bioactive peptides, play crucial roles in multiple physiological functions such as hormonal messengers, antimicrobial agents, immune performance, cytokines, signal transduction, antiviral agent, cell‐cell communication, and protease inhibitors (Schrader, 2018). Peptidomics has several important applications, including candidate bioactive peptides, disease biomarkers, neuropeptidomics, and mapping dietary protein digestion (Dallas et al, 2015).…”
Section: Current Status Of Multiomics Studies Of Pasmentioning
confidence: 99%
“…Based on this evidence, thiazolidinediones might be one way to clinically manage Cushing's disease (Heaney et al, 2002). Acetylsalicylic acid or survivin small‐molecule inhibitors decreased proliferation and regulated cell cycles (S and G2/M phase) to inhibit PA cell growth (Németh et al, 2018). The downregulated expression of lncRNA H19 was significantly associated with PA tumorigenesis and progression (Wu et al, 2018).…”
Section: Signaling Pathway‐based Therapeutic Targets and Drugs For Pasmentioning
confidence: 99%
“…In the publication by Németh K et al, [8], they described the role of survivin in pituitary adenomas (PAs) as well as a new mechanism by which the apoptotic effect of ASA can be used to target PA cells. Representing approximately 20% of intracranial neoplasms, PAs are considered the third most frequent intracranial neoplastic tumor type, shadowing only meningiomas and glioblastomas [9].…”
mentioning
confidence: 99%
“…The current study [8] is a useful and well-written addition to the literature involving antitumor effects of ASA via the survivin pathway. They demonstrated that from the various pituitary tissue types they analyzed, survivin was overexpressed only in the NFPAs.…”
mentioning
confidence: 99%